Предмет: Алгебра,
автор: yaltis
(-8a-b)(-b+6a)=
(2a+3b^3)(3b^3-2a)=
(4b+1)(1-4b)
Ответы
Автор ответа:
0
(- 8а - b)( -b + 6a) = 8ab - 48a^2 + b^2 - 6ab = - 48a^2 + 2ab + b^2
(2a + 3b^3)(3b^3 - 2a) = 6 ab^3 - 4a^2 + 9b^6 - 6ab^3 = - 4a^2 + 9b^6
(4b + 1)(1 - 4b) = 4b - 16b^2 +1 - 4b = -16b^2 + 1
(2a + 3b^3)(3b^3 - 2a) = 6 ab^3 - 4a^2 + 9b^6 - 6ab^3 = - 4a^2 + 9b^6
(4b + 1)(1 - 4b) = 4b - 16b^2 +1 - 4b = -16b^2 + 1
Похожие вопросы
Предмет: Қазақ тiлi,
автор: gabdullinanoni
Предмет: Физика,
автор: sugarbulka
Предмет: Қазақ тiлi,
автор: anelyasubykhan
Предмет: Математика,
автор: shovda1988
Предмет: История,
автор: ALENKA20141998